The Relationship of Internal Factors With The Response of Bukit Madu Farmer Women In Making Ginger-Flavored Milk Candy In Madukoro Village, Magelang Regency - Zulfikhar, Rosa; Saputra, Yudhi Eka; Wibowo, Haris Tri; Akbarrizki, Muzizat; Winarno, Kodrat (Jurnal Pengembangan Penyuluhan Pertanian, 2024)
The study was conducted from March 2022 to May 2023 in Madukoro Village, Kajoran District, Magelang Regency with the aim of determining the response of farmer women in making ginger-flavored milk candy and knowing the relationship between internal factors (age, education level, farming experience, number of family members, and income level) with responses in making ginger-flavored milk candy. Sampling of 30 people using saturated sampling technique. Data collection techniques are carried out by means of interviews and observations. The variables observed were age, education level, farming experience, number of family members, and income level and response consisting of aspects of knowledge, attitudes, skills. The data analysis method used was descriptive analysis to determine the response of peasant women, while statistical analysis of spearman rank correlation was used to determine the relationship between the characteristics of peasant women to the response. The results of data analysis showed that the response of peasant women in Madukoro Village in making ginger-flavored milk candy was in the high category. The relationship between age, education level and farming experience with responses of 0.000 (p<0.05), 0.004 (p<0.05), and 0.000 (p<0.5). The age variable was significantly related (P< 0.01) to the response of Bukit Madu peasant women group members in making ginger-flavored goat milk candy. Good responses were dominated by respondents with productive age, high level of education, and long farming experience, the number of family dependents and income level were not related to the response. The effectiveness of counseling indicates that extension activities.